MARKET SEGMENTATION ANALYSIS TO INCREASE THE EFFECTIVENESS OF MARKETING STRATEGIES - Potton, Zainal; Baharuddin, Baharuddin (IJMA (Indonesian Journal of Management and Accounting), 2024)
Market segmentation analysis is a process for understanding and dividing the market into smaller groups or segmentation based on different characteristics, such as demographics, behavior, or needs. The goal of research is to understand the needs, preferences and behavior of different consumers so that companies can develop more effective marketing strategies for each segment. The research method used in this research is qualitative by identifying segmentation variables or criteria that are used to divide the market into different segments including demographics age, gender, income, geography (geographical location), psychographics values, interests, lifestyle , or behavior (purchasing habits, brand loyalty). The result of this research is market segmentation, identifying criteria that can be used to divide the market into smaller segments. These criteria may include demographic age, gender, income, geographic (geographic location), psychographic (lifestyle, values), or behavioral (purchasing habits, brand loyalty.